Non-negotiable: Non-dialogical feedback strategies in mid-term exams ina university of Lima in an intercultural context - Arcela Pérez, Magaly (2020)
In a context of cultural and social insertion of students from disadvantaged sectors, in this paper, which is based on my master’s thesis (2017), I examine the feedback given by two university professors in the mid-term exams of the History and Ethics courses. This study was carried out from the critical conception of language as social practice (Fairclough, 1992) and the Appraisal Theory (Martin and White, 2005). The aim of this research is to explain the ways in which feedback is conveyed in the mid-term exams and to find out whether the discursive strategies employed by these teachers are constructed in a dialogical way. The results show professors’ preference for evaluating negatively and for using linguistic strategies that close the channels of dialogue and reproduce hierarchical relations.